2020
DOI: 10.1177/1039856220901466
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the practice of electroconvulsive therapy (ECT) in a Victorian health service before and after the Mental Health Act 2014

Abstract: Objective: The aim of the project was to identify changes in the practice of electroconvulsive therapy (ECT) in a metropolitan mental health service before and after the Mental Health Act 2014 (2014 Act) in Victoria. Method: Retrospective clinical file audit of ECT administration across all three sites at Eastern Health (EH) two years before and two years after introduction of the 2014 Act. Results: There was a statistically significant decrease in the number of compulsory ECT treatments and in the number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…2 A key finding of Lee et al was a significant reduction in the total number of patients per month with the MHA 2014. 1 We found a similar decline in ECT use, i.e. 14.83% reduction in ECT use per 1000 admissions and 19.91% reduction in the ECT of utilisation per 100,000 persons.…”
Section: Psychiatrysupporting
confidence: 69%
See 4 more Smart Citations
“…2 A key finding of Lee et al was a significant reduction in the total number of patients per month with the MHA 2014. 1 We found a similar decline in ECT use, i.e. 14.83% reduction in ECT use per 1000 admissions and 19.91% reduction in the ECT of utilisation per 100,000 persons.…”
Section: Psychiatrysupporting
confidence: 69%
“…Lee et al found a significant reduction in the number of compulsory ECT treatments. 1 We only found a marginal decline in the rate of involuntary consent in the beginning of ECT course. However, a significantly lower proportion of patients finished ECT episodes under involuntary consent.…”
mentioning
confidence: 58%
See 3 more Smart Citations